Analisis Penggunaan Kalimat pada Teks Laporan Hasil Observasi dalam Buku Ajar Kelas X SMA Kurikulum Merdeka - Dinda Puspita Rini; Putri Aji Rahayu; Riska Setyowati Siwi; Zidna Fitriana; Asep Purwo Yudi Utomo; Oktarina Puspita Wardani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In the Indonesian language textbook for class X SMA Merdeka curriculum, an error was found, namely in writing a sentence that did not comply with linguistic rules in the form of using inappropriate punctuation, using wrong diction, and applying conjunctions that were not appropriate. Effective sentences are absolutely used so that the reader can understand the information obtained. Errors found in the text of the observation report were the main factor in this research. This study aims to find out the mistakes in writing sentences contained in the text of the report on observations of Class X SMA Merdeka Curriculum. By doing this error analysis, the teaching materials used will make it easier for students to learn. The benefits obtained after carrying out the analysis are knowing the errors contained in the textbook which can then be analyzed and adapted to the learning needs of students. The approach used is a qualitative descriptive approach and a paradigmatic approach. The data comes from the report's text on the results of observations contained in the textbook. The method used is to read the entire text, find errors, analyze, classify errors, and correct these errors. The text of the observation report is a report in the form of the results of observation or research activities that contain facts obtained in the field. The results obtained from this study are the discovery of three errors, namely the application of inappropriate punctuation, the application of wrong diction, and the application of conjunctions that are not appropriate. These errors can occur because students do not understand the knowledge and skills used when writing a report.